PENGARUH KUALITAS KEHIDUPAN KERJA TERHADAP NIATAN BERHENTI KERJA DENGAN MEDIASI KEPUASAN KERJA DAN KINERJA KARYAWAN - Indah Handayani; Edi Purwanto (Journal of Business & Applied Management, 2018)
This research aims, while exploring the mediating effect of job satisfaction and job performance,to know and explain how quality of work life influence the turnover intentions at the PT. Bina KaryaPrima. Research study samples include 103 of the PT. Bina Karya Prima employees. Data collecting usedquestionnaires, which were shared directly. Data was analysed using the Structural Equation Model(SEM) with PLS software. Research results show that: (1) job satisfaction has a negative and significantinfluence on the turnover intentions, (2) job performance has a negative and significant influence on theturnover intentions, (3) job satisfaction has not significant influence on the job performance, (4) qualityof work life has not a significant influence on the job satisfaction, and (5) quality of work life has apositive and significant influence on the job performance.Keywords: turnover intentions, quality of work life